Achieving Success As a 21st Century Manager. - Frost, Dean E. (New York : Business Expert Press, 2021)
This book is about taking personal control of your management career by planning for your development outside of training sessions or university degree programs. Careers and organizations are changing rapidly so personalizing your own training and competency development is critical. Included in this book are self-evaluations for cognitive competence, virtual competence, emotional competence, cross-cultural competence, socialization competence, health competence, and competencies in spotting leadership differences and situational recognition.
Cover -- Halftitle -- Title -- Copyright -- Dedication -- Description -- Contents -- Chapter 1: Introduction to an Action Learning Approach to Management Development -- Chapter 2: Leadership Differences Competence -- Chapter 3: Situational Recognition Competence -- Chapter 4: Cognitive Competence -- Chapter 5: Virtual Competence -- Chapter 6: Emotional Competence -- Chapter 7: Cross-Cultural Competence -- Chapter 8: Socialization Competence -- Chapter 9: Health Competence -- References -- About the Author -- Index -- Adpage -- Backcover.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Management; Leadership; Electronic books